INFLUNCE OF GROWTH REGULATORS ON CALLUS INDUCTION OF CITRUS VOLKAMERIANA IN VITRO - & Hamad, Al- Khazali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This  research  was  conducted  in  the  plant  tissue  culture  Lab. College  of Agriculture / University  of  Baghdad  from  February to  October  2015. The aim  of  the  study  was  investigating  the  influences  of  combinations  of  Naphthalene  acetic  acid (NAA) , Thidiazuron (TDZ) Spermidine  (Spd. ) and 2,4-Dichlorophenoxy  acetic  acid (2,4-D) , Benzyl  adenine (BA) on callus  induction  and  adventitous  shoot  regeneration  originated  from  cotyledon  of  Citrus volkameriana  seeds. Seeds  were  disinfested  with 0.1 % of  HgCl2  for 15 minutes. The MS  medium  supplemented  with  (0.0,1.5 , 3.0 ) mg L-1  NAA in combination with (0.0, 0.05, 0.1) mg L-1  TDZ and (0.0, 0.5 ,1.0) mg L-1 Spd. and MS medium supplemented with (0.0, 1.5 , 3.0) mg L-1  2,4-D in combination with (0.0 ,1.0 , 2.0 )  mg L-1  BA and (0.0 ,0.5 , 1.0) mg L-1  Spd. the  interaction between 1.5 mg L-1  NAA and (0.05 , 0.1)  mg L-1  TDZ and the interaction between 3.0 mg L-1  NAA and (0.05 ,0.1) mg L-1  TDZ with all concentrations of Spd.   gave  the  highest  percentage of  callus  induction  100 % . While  the  MS  medium  supplemented  with  3 mg L-1 of  2,4-D in  combination  with  all  concentrations  of  BA  and  spd.  gave  the  highest  percentage 100 % of  callus induction. Results showed that  MS medium supplemented  with 1.5 mg L-1  NAA in combination  with  0.1 mg L-1 TDZ and  1.0 mg L-1 spd.  gave  the  highest  values  of  fresh  and  dry  weight  of  callus  (668.8, 44.59 ) mg  respectively . While  the  MS  medium  supplemented  with  3 mg L-1 2,4-D  in combination with 1.0 mg  L-1  spd.  And 0.0 mg L-1 BA gave  the  highest  values  of  fresh  and  dry  weight  of  callus  (709.2 , 47.28 ) mg  respectively.